Analisis Sentimen Komentar Youtube Tentang Resesi Global 2023 Menggunakan LSTM - Ari Hendrawan; Enny Itje Sela (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The COVID-19 pandemic that occurred in 2020 caused the economy to decline due to declining economic activity, making companies decide to lay off some workers so that the unemployment rate increased. This makes economic activists predict that there will be a global recession in 2023, Youtube as a video-sharing platform is one of the places to discuss through the comment’s column. The increasing number of YouTube users is one of the references for sentiment analysis using data taken from video comments. Long Short-Term Memory (LSTM) is used to perform sentiment analysis, with 500 data divided into training data and test data, resulting in the highest accuracy of 90% training data and 76% test data. This result is obtained from the configuration of the LSTM architecture with dense layers using sigmoid activation and 50 epochs.